2019
DOI: 10.1002/sej.1334
|View full text |Cite
|
Sign up to set email alerts
|

Different expectations: A comparative history of structure, experience, and strategic alliances in the U.S. and U.K. poultry sectors, 1920–1990

Abstract: Research Summary This comparative historical analysis demonstrates how memory and reflexive interpretations of the past can shape entrepreneurial willingness to collaborate with larger firms in an industry. Emphasizing the importance of spatial metaphors and periodization for developing historical knowledge, the paper focuses on how the historical space of experience explains how entrepreneurs make strategic choices regarding collaboration under conditions of complexity and uncertainty. Comparing the U.S. and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 97 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…Despite the promising benefits of alliance, this organizational structure suffers from different challenges, including asymmetry of collaborators' motives, uncertainty of outcomes, unpredictability of partner behavior, and opportunism (Gulati, Wohlgezogen, & Zhelyazkov, 2012). These issues can affect the alliance success (Dyer & Singh, 1998; Koka & Prescott, 2008), leading to high failure rate (Godley & Hamilton, 2020), whereby many companies fail to get the hoped‐for outcomes from their alliances (Lokshin et al, 2011). As such, researchers have shown that between 30 and 70% of alliances do not live up to expectations (Lhuillery & Pfister, 2009; Park & Ungson, 2001).…”
Section: Alliance Management Capability: a Source For The Relational ...mentioning
confidence: 99%
“…Despite the promising benefits of alliance, this organizational structure suffers from different challenges, including asymmetry of collaborators' motives, uncertainty of outcomes, unpredictability of partner behavior, and opportunism (Gulati, Wohlgezogen, & Zhelyazkov, 2012). These issues can affect the alliance success (Dyer & Singh, 1998; Koka & Prescott, 2008), leading to high failure rate (Godley & Hamilton, 2020), whereby many companies fail to get the hoped‐for outcomes from their alliances (Lokshin et al, 2011). As such, researchers have shown that between 30 and 70% of alliances do not live up to expectations (Lhuillery & Pfister, 2009; Park & Ungson, 2001).…”
Section: Alliance Management Capability: a Source For The Relational ...mentioning
confidence: 99%
“…However, it is not clear how their autonomy (that is, the freedom of action of individuals or groups that allows people to come up with an idea or viewpoint and fully develop it) can affect a firm´s entrepreneurial orientation (Lumpkin and Dess, 1996), and hence lead to the success of the partnership. Although the research field on entrepreneurship and partnership provides valuable information based on knowledge exploitation strategies, there are only a limited number of studies related to entrepreneurial orientation (EO) and partnership (PT) (Chen and Wang, 2020; Godley and Hamilton, 2020; Li et al , 2017; Oliveira Junior et al , 2016; Seo, 2020; Teng, 2005; Tokman et al , 2020), between EO and competitive aggressiveness (CA) (Oliveira Junior, 2015), especially in light of the mediating effect of market orientation (MO) on the EO–PT relationship (Tjahjadi et al , 2020; Wales et al , 2011) and autonomy as an antecedent of EO (Al Mamun et al , 2017; Gartner, 1985; Gil-López et al , 2020; Simsek et al , 2010; Wales et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We begin in the early 19 th century as this period aligns with Taylor's ( 2004) account of the origins of modern social imaginaries and because the decline in traditional apprenticeships based on the legal and social authority of masters and the emergence of new educational models to fill this void constituted a major shift in the educational landscape throughout much of the Western world (Aldrich, 1999). Building on Godley and Hamilton (2020), we use a comparative history design to identify similarities and differences in the evolution of entrepreneurship education and to move beyond U.S.-centric accounts. Germany represents an especially useful point of comparison because its pioneering and influential role in the development of business education had a strong influence on similar developments in much of Continental Europe and in Japan (Engwall, 2004;Locke, 2008), and because its role in the development of the model of the modern research university had a more general long-term influence on higher education (Rüegg, 2004).…”
Section: Scope and Methodsmentioning
confidence: 99%